Synthesis and properties of ceria based electrolyte for IT-SOFCs. (28th September 2016) - Yang, Jie; Ji, Bifa; Si, Jingyu; Zhang, Quanzheng; Yin, Qiyi; Xie, Jingsong; Tian, Changan
Abstract: Fluorite oxides Ce0.8 Y0.18 M0.02 O2 − δ (denoted as MYDC for M = Ca, Sr, Fe and La), were prepared by the sol–gel method used as electrolytes for intermediate-temperature solid oxide fuel cells (IT-SOFCs). X-ray diffraction data show that all the compositions were obtained with highly phase-pure cubic fluorite structure. The relatively density of all the samples sintered at 1400 °C is more than 95%. Surface morphology has been studied by scanning electron microscope showing a dense microstructure. AC impedance spectroscopy measurements have been carried out to study the ionic conductivity of the samples in the temperature range 400–800 °C. In all composition, Ce0.8 Y0.18 La0.02 O2 − δ shows the maximum conductivity of 0.057 S/cm at 800 °C and shows a good prospect of application in IT-SOFCs. Highlights: Fluorite oxides Ce0.8 Y0.18 M0.02 O2 − δ (denoted as MYDC for M = Ca, Sr, Fe and La), were prepared by the sol–gel method. The relatively density of all the samples sintered at 1400 °C is more than 95%. Ce0.8 Y0.18 La0.02 O2 − δ shows the maximum conductivity of 0.057 S/cm at 800 °C among all the compositions investigated.